Sunlight Assisted Degradation of Linear Alkylbenzene Sulfonate by Floating Catalyst TiO2-Coconut Fiber - Sugandi, Didiek; Agustiawan, Deri; Wijayanto, Ericco; Vebriyanti, Lo Mei Ly; Panaya, Gabriela Yenti Landang; Wahyuni, Nelly (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2023)
The increasing number of laundry businesses in Pontianak causes increased laundry waste, which is dangerous for health and the environment because anionic surfactants such as Linear Alkylbenzene Sulfonate (LAS) are hard degradable. Photocatalyst is a method that can be used to degrade the LAS structure. TiO2 carried in coconut fiber can optimize sunlight irradiation in degrading LAS content when light reaches the water's surface. This study aims to determine the characteristics and optimum activity time of photocatalyst TiO2-coconut fiber in degrading LAS. Photocatalyst characterization was carried out using XRD, XRF, and DR-UV, while the optimum activity test of photocatalysts in degrading LAS was carried out using a UV-Vis spectrophotometer. XRD diffractogram analysis showed the peaks of coconut fiber at 2θ = 22.2º, 34.8º and TiO2 at 2θ = 25.3º, 37.8º, 48.1º, 55.1º, and 62.1º. The TiO2 attached to the fiber after being synthesized was 21.12%. The band gap of TiO2 and TiO2-coconut fiber is 3.21 and 3.18 eV, with light absorption at 386.5 and 390.3 nm. Photocatalyst was carried out in LAS with a mass ratio of TiO2 and coconut fiber of 20:80; 30:70; 40:60, and 50:50 w/w with a time range of 0, 30, 60, 90, and 120 minutes. The results of photocatalysis of TiO2-coconut fiber in a ratio of 20:80 w/w showed the optimum photocatalytic activity at 120 minutes with the highest degradation rate of 80.43%. This research is expected to be applied as an alternative to handling LAS in laundry industry waste.